2017
DOI: 10.1080/21679169.2017.1332683
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of physical activity following total hip and knee arthroplasty: data from the English Longitudinal Study of Ageing (ELSA) cohort

Abstract: Purpose: To determine the prevalence and trajectory of physical activity levels in people before and after total hip (THA) and total knee arthroplasty (TKA). Results: There was a statistically significant decrease in physical activity from the pre-arthroplasty phase to the operative-recovery phase (p<0.01), and a significant increase in physical activity from the operative-recovery phase to final follow-up (p=0.05). However, overall there was no significant change in physical activity from pre-operatively to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Twelve articles reported on subjects with various types of arthroplasties [ 22 , 27 , 34 , 53 , 61 , 66 , 80 , 91 , 99 , 102 , 105 , 111 ]. Most results found in the studies using more than one type of arthroplasty were, as could be expected, comparable to the results described above.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve articles reported on subjects with various types of arthroplasties [ 22 , 27 , 34 , 53 , 61 , 66 , 80 , 91 , 99 , 102 , 105 , 111 ]. Most results found in the studies using more than one type of arthroplasty were, as could be expected, comparable to the results described above.…”
Section: Resultsmentioning
confidence: 99%
“…Older adults often have broken sleep due to medication, 19 or needing to void urine; 29 so it is reasonable to conclude that attention to sleep issues or bladder training may decrease the risk of fatigue associated with a lack of sleep. 30 One small (n = 44) prospective study in the Netherlands demonstrated a significant increase in participants' sedentary behaviour (measured by accelerometry) four years after total hip or knee replacement, 6 however factors associated with or predictive of increased sedentary behaviour were not discussed. No pre-surgery predictors of excessive sedentary behaviour were identified by our multivariate model, however excessive sedentary behaviour and lack of energy at one year after surgery significantly predicted excessive sedentary behaviour at five years.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 The studies varied in their design and included retrospective, 8,9 cross-sectional, 4,7,10,11 and prospective 5,12,15 investigations. Most studies used questionnaires to collect data, 4,6,9,11,12,14,15 although two used accelerometers. 5,10 Only three studies reported whether the WHO physical activity guidelines had been met by participants, giving a range of results from 5% to 42%.…”
Section: Introductionmentioning
confidence: 99%